Multi-wavelength light emission from InGaN nanowires on pyramid-textured Si(100) substrate grown by stationary plasma-assisted molecular beam epitaxy. Issue 16 (7th April 2020) - Wang, Peng; Chen, Hedong; Wang, Hao; Wang, Xingyu; Yin, Hongjie; Rao, Lujia; Zhou, Guofu; Nötzel, Richard
Abstract : The In composition of InGaN nanowires grown on a pyramid-textured Si substrate was laterally tuned beyond the nanoscale with stationary plasma-assisted molecular beam epitaxy. Abstract : We demonstrate multi-wavelength light emission from InGaN nanowires (NWs) monolithically grown on pyramid-textured Si(100) substrates by plasma-assisted molecular beam epitaxy (MBE) under stationary conditions. Taking advantage of the highly unidirectional source material beam fluxes, the In content of the NWs is tuned on the different pyramid facets due to varied incidence angle. This is confirmed by distinct NW morphologies observed by scanning electron microscopy (SEM) and by energy-dispersive X-ray (EDX) element mapping. Photoluminescence and cathodoluminescence (CL) reveal multiple lines originating from InGaN NWs on the different pyramid facets. The anomalous temperature dependence of the emission wavelength results from carrier redistribution between localized or confined states, spontaneously formed within the NWs due to composition fluctuations, verified by high-resolution EDX elemental analysis. First-principles calculations show that the pyramid facet edges act as a barrier for atom migration and enhance atom incorporation. This leads to uniform composition within the facets for not too high a growth temperature, consistent with the SEM, EDX and CL results. At elevated temperature, InGaN decomposition and In desorption are enhanced on facets with low growth rate, accompanied by Ga inter-facet migration, leading to non-uniform composition over the Ga migration length which is deduced to be around 580 nm. Our study presents a method for the fabrication of multi-wavelength light sources by highly unidirectional MBE on textured Si substrates towards color temperature-tunable solid-state lighting and RGB light-emitting diode displays.